Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To solve the problem, we start with the given information and the relationship between [tex]\( y \)[/tex] and [tex]\( x \)[/tex].
1. Understanding Direct Proportion:
- We know that [tex]\( y \)[/tex] is directly proportional to the cube root of [tex]\( (x + 3) \)[/tex]. This can be mathematically represented as:
[tex]\[ y = k \cdot \sqrt[3]{x + 3} \][/tex]
where [tex]\( k \)[/tex] is the constant of proportionality.
2. Given Values:
- When [tex]\( x = 5 \)[/tex], [tex]\( y = \frac{2}{3} \)[/tex].
3. Finding the Constant of Proportionality [tex]\( k \)[/tex]:
- Substitute [tex]\( x = 5 \)[/tex] and [tex]\( y = \frac{2}{3} \)[/tex] into the equation [tex]\( y = k \cdot \sqrt[3]{x + 3} \)[/tex]:
[tex]\[ \frac{2}{3} = k \cdot \sqrt[3]{5 + 3} \][/tex]
- Simplify inside the cube root:
[tex]\[ \frac{2}{3} = k \cdot \sqrt[3]{8} \][/tex]
- Since the cube root of 8 is 2, we have:
[tex]\[ \frac{2}{3} = k \cdot 2 \][/tex]
- Solve for [tex]\( k \)[/tex]:
[tex]\[ k = \frac{\frac{2}{3}}{2} = \frac{2}{3} \cdot \frac{1}{2} = \frac{1}{3} \][/tex]
4. Using [tex]\( k \)[/tex] to Find [tex]\( y \)[/tex] When [tex]\( x = 24 \)[/tex]:
- Substitute [tex]\( x = 24 \)[/tex] and [tex]\( k = \frac{1}{3} \)[/tex] back into the equation:
[tex]\[ y = \frac{1}{3} \cdot \sqrt[3]{24 + 3} \][/tex]
- Simplify inside the cube root:
[tex]\[ y = \frac{1}{3} \cdot \sqrt[3]{27} \][/tex]
- Since the cube root of 27 is 3, we have:
[tex]\[ y = \frac{1}{3} \cdot 3 = 1 \][/tex]
Therefore, when [tex]\( x = 24 \)[/tex], the value of [tex]\( y \)[/tex] is [tex]\( \boxed{1} \)[/tex].
1. Understanding Direct Proportion:
- We know that [tex]\( y \)[/tex] is directly proportional to the cube root of [tex]\( (x + 3) \)[/tex]. This can be mathematically represented as:
[tex]\[ y = k \cdot \sqrt[3]{x + 3} \][/tex]
where [tex]\( k \)[/tex] is the constant of proportionality.
2. Given Values:
- When [tex]\( x = 5 \)[/tex], [tex]\( y = \frac{2}{3} \)[/tex].
3. Finding the Constant of Proportionality [tex]\( k \)[/tex]:
- Substitute [tex]\( x = 5 \)[/tex] and [tex]\( y = \frac{2}{3} \)[/tex] into the equation [tex]\( y = k \cdot \sqrt[3]{x + 3} \)[/tex]:
[tex]\[ \frac{2}{3} = k \cdot \sqrt[3]{5 + 3} \][/tex]
- Simplify inside the cube root:
[tex]\[ \frac{2}{3} = k \cdot \sqrt[3]{8} \][/tex]
- Since the cube root of 8 is 2, we have:
[tex]\[ \frac{2}{3} = k \cdot 2 \][/tex]
- Solve for [tex]\( k \)[/tex]:
[tex]\[ k = \frac{\frac{2}{3}}{2} = \frac{2}{3} \cdot \frac{1}{2} = \frac{1}{3} \][/tex]
4. Using [tex]\( k \)[/tex] to Find [tex]\( y \)[/tex] When [tex]\( x = 24 \)[/tex]:
- Substitute [tex]\( x = 24 \)[/tex] and [tex]\( k = \frac{1}{3} \)[/tex] back into the equation:
[tex]\[ y = \frac{1}{3} \cdot \sqrt[3]{24 + 3} \][/tex]
- Simplify inside the cube root:
[tex]\[ y = \frac{1}{3} \cdot \sqrt[3]{27} \][/tex]
- Since the cube root of 27 is 3, we have:
[tex]\[ y = \frac{1}{3} \cdot 3 = 1 \][/tex]
Therefore, when [tex]\( x = 24 \)[/tex], the value of [tex]\( y \)[/tex] is [tex]\( \boxed{1} \)[/tex].
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.